2004
DOI: 10.1128/jcm.42.11.4956-4960.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Rapid Immunochromatographic Assay for Identification of Candida albicans and Candida dubliniensis

Abstract: Candida dubliniensis was first established as a novel yeast species in 1995. It is particularly associated with recurrent episodes of oral candidosis in human immunodeficiency virus (HIV)-infected patients, but it has also been detected at other anatomical sites and at a low incidence level in non-HIV-infected patients. It shares so many phenotypic characteristics with C. albicans that it is easily misidentified as such. No rapid, simple, and commercial test that allows differentiation between C. dubliniensis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 38 publications
0
20
0
3
Order By: Relevance
“…All had been identified by a number of techniques, including PCR based on the intron sequence of the ACT1 gene or immunofluorescence with a specific monoclonal antibody (20). Fresh clinical isolates of C. albicans and C. dubliniensis were also investigated, and their identities were confirmed by growth on modified Pal's agar (1,19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All had been identified by a number of techniques, including PCR based on the intron sequence of the ACT1 gene or immunofluorescence with a specific monoclonal antibody (20). Fresh clinical isolates of C. albicans and C. dubliniensis were also investigated, and their identities were confirmed by growth on modified Pal's agar (1,19).…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it was reported that the two species could be distinguished by culture on Staib agar, Pal's agar, modified Pal's agar, and casein agar, on which only C. dubliniensis produces abundant chlamydospores and rough colonies (1,2,3,24,28). We also described an immunochromatographic assay differentiating between C. albicans and C. dubliniensis, but C. dubliniensis was identified only by default, owing to the specificity of the monoclonal antibodies (MAbs) (19). The aim of the present study was to produce a monoclonal antibody specific for C. dubliniensis cells and to investigate its potential use in a rapid latex agglutination test for identifying C. dubliniensis colonies.…”
mentioning
confidence: 99%
“…The assay exploits the lateral-flow technology that has been used to date in tests for the detection of viruses, bacteria, and toxins (11,13,(28)(29)(30) and, most famously, for the home pregnancy tests first introduced by Unipath in 1988. While immunochromatographic assays have been developed for the identification of Candida species (19) and for the detection of fungi in soil (36,37), this is the first time, to the best of the author's knowledge, that an LFD has been developed for the detection of Aspergillus antigens in human serum.…”
mentioning
confidence: 99%
“…Moreover, considerable experience is necessary for correct phenotypic identification of the steadily expanding range of pathogenic and opportunistic fungi. The discrepant result of one clinical specimen identified as C. dubliniensis by the Luminex assay and C. albicans by blood culture (Table 5) could be attributable to the major phenotypic (22) but only limited genetic similarities between these two species which have likely led to incorrect typing by routine fungus culture. Unequivocal identification of C. albicans and C. dubliniensis, however, may be relevant for the most appropriate antifungal treatment.…”
Section: Discussionmentioning
confidence: 99%